Analisis Penggunaan Kandoushi Dalam Game Genshin Impact - Putri, Cahaya Fatihah Dedy; Nurhayati, Silvia (Vocational College of Diponegoro University, 2024)
Kandoushi or interjection is part of the Japanese word class or 品詞分類 (hinshi bunrui) which functions to express emotions or feelings, such as surprise, happiness, admiration, doubt, and so on. Kandoushi is often found in Japanese language communication and Japanese language media such as anime, comics, films, dramas, and even in games. In Japanese language learning, kandoushi is often found in Choukai (listening) and Kaiwa (conversation) activities. On the other hand, based on the results of a preliminary study in the form of a simple interview, there are still many students of the Japanese Language Education Study Program who do not understand the function, meaning and types of kandoushi. Therefore, the purpose of this study is to explain the types, functions, and meanings of kandoushi in the Genshin Impact game. The data collection technique in this study is the listening and note-taking technique. The data source in this study is a game entitled Genshin Impact. This game was chosen because it is one of the games that is popular among fans of Japanese popular culture, including students of the Japanese Language Education Study Program. In addition, various variations of kandoushi forms were found in character dialogues in the Genshin Impact story. The collected data were then analyzed based on Takeshi's (2019) kandoushi type theory. The results of this study were the discovery of 109 speech data containing kandoushi. The 109 data were classified into 6 types of kandoushi. The classification was determined based on the function of each form of kandoushi. Various functions and meanings of kandoushi were also found in the Genshin Impact game.